Use of Robotics and IoT in Basic Education: A systematic mapping study - Ribeiro, Carlos Eduardo; Turossi, Marcos Tulio C.; Trindade, Daniela de Freitas G.; Palácios, Rodrigo H. Cunha; Todt, Eduardo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
Robotics and the Internet of Things (IoT) have emerged as powerful tools to enhance teaching and learning processes, aligning with the National Common Curriculum Base (BNCC). This systematic mapping study provides an overview of existing research on the use of robotics and IoT in basic education in the context of the BNCC. It involved a comprehensive search and analysis of relevant articles in scientific databases. The search was carried out with the complete string containing all keywords and their synonyms in the ACM, IEEE, Scielo, Scopus, and CAPES periodic databases. Seven articles were selected, focusing on their approach to the Base National Comum curriculum, educational methodologies, concepts addressed, kits and simulators used, validation and testing, and contributions to the teaching of informatics. The authors present an innovative pedagogical approach based on educational robotics, as well as empirical evidence of its effectiveness in improving students’ skills.